Analysis of an Online Match Discussion Board: Improving the Otolaryngology–Head and Neck Surgery Match. (30th December 2014) - Kozin, Elliott D.; Sethi, Rosh K. V.; Lehmann, Ashton; Remenschneider, Aaron K.; Golub, Justin S.; Reyes, Samuel A.; Emerick, Kevin S.; Lee, Daniel J.; Gray, Stacey T.
Abstract : Objective: "The Match" has become the accepted selection process for graduate medical education. Otomatch.com has provided an online forum for Otolaryngology–Head and Neck Surgery (OHNS) Match‐related questions for over a decade. Herein, we aim to delineate the type of posts on Otomatch to better understand the perspective of medical students applying for OHNS residency. Study Design: Retrospective review of an OHNS Match‐related online forum. Subjects and Methods: Subjects were contributors to an OHNS Match‐related online forum. Posts on Otomatch between December 2001 and April 2014 were reviewed. The title of each thread and number of views were recorded for quantitative analysis. Each thread was organized into 1 of 6 major categories and 1 of 18 subcategories. National Resident Matching Program (NRMP) data were utilized for comparison. Results: We identified 1921 threads corresponding to over 2 million page views. Over 40% of threads were related to questions about specific programs, and 27% were discussions about interviews. Views, a surrogate measure for popularity, reflected different trends. The majority of individuals viewed posts on interviews (42%), program‐specific questions (20%), and how to rank programs (11%). There was an increase in viewership tracked with a rise in applicant numbers based on NRMP data. Conclusion: Our study provides an in‐depth analysis of a popular discussion forum for medical students interested in the OHNS Match process. The most viewed posts are about interview dates and questions regarding specific programs. We provide suggestions to address unmet needs for medical students and potentially improve the Match process.